Immunostimulatory Activity of Protein Hydrolysate from Oviductus Ranae on Macrophage In Vitro. (21st December 2014) - Huang, Di; Yang, Lubing; Wang, Chenlu; Ma, Sihui; Cui, Li; Huang, Shiyang; Sheng, Xia; Weng, Qiang; Xu, Meiyu
Abstract : Oviductus Ranae is the dry oviduct of Rana chensinensis, which is also called R. chensinensis oil. Oviductus Ranae is a valuable Chinese crude drug and is recorded in the Pharmacopoeia of the People's Republic of China. The aim of this study was to investigate the immunostimulatory activity of protein hydrolysate of Oviductus Ranae (ORPH) and to assess its possible mechanism. Immunomodulatory activity of ORPH was examined in murine macrophage RAW 264.7 cells. The effect of ORPH on the phagocytic activity of macrophages was determined by the neutral red uptake assay. After treatment with ORPH, NO production levels in the culture supernatant were investigated by Griess assay. The mRNA and protein expressions of inducible nitric oxide synthase (iNOS) were detected by RT-PCR and Western blotting. The production of TNF- α, IL-1 β, and IL-6 after treatment with ORPH was measured using ELISA assay. In addition, NF- κ B levels were also investigated by Western blot. The results showed that ORPH enhanced the phagocytosis of macrophage, increased productions of TNF- α, IL-1 β, IL-6, and NO in RAW 264.7 cells, and upregulated the mRNA and protein expression of iNOS. Besides, NF- κ B, levels in RAW 264.7 cells were elevated after ORPH treatment. These findings suggested that ORPH might stimulate macrophage activities by activating the NF- κ B pathway.